Fifty Years After, czyli kilka refleksji o dzisiejszej kulturze młodzieżowej - Jakubowski, Witold (Studia Edukacyjne, 2020)
The article discusses the problem of recent changes in so-called “teenage culture”. Theoretical bases of the cultural anthropologic conception were provided by Margaret Mead. According to the author, “teenage culture” is different in each type of Mead’s culture types. Insignificant in the post-figurativstage, “teenage culture” is definitelydistinct in configurativetype in terms of separate aesthetics. This is exemplifiedby teenage subcultures, whose members contest dominant culture patterns (associated with adults). The main question concerns the role of “teenage culture” in the pre-figurativeculture – the modern world. Is the difference between the adults’ and young people’s perspectives evident in “teenage culture”? Moreover, is there a real “teenage culture” nowadays?